DESAIN TUNGKU PENGERING MOBILE BERBAHAN BAKAR SERBUK GERGAJI - Tamaria Panggabean; Tri Tunggal; Endo Argo Kuncoro (Jurnal Teknologi Pertanian Andalas, 2024)
This research was motivated by the use of a fixed bed furnace. Fixed bed furnaces are less effective because their use is fixed.  The purpose of this research was to design a mobile drying furnace fueled by sawdust biomass.  This research uses an experimental method with 3 stages of design, namely design approach, functional design and structural design. The data obtained were analyzed descriptively. The result of this research is a mobile drying furnace designed consisting of a fuel feeder, fuel channel, hopper, combustion chamber and heat exchanger chamber, chimney and furnace outlet channel and channel after the fan that can function properly. Furnace testing was carried out using sawdust fuel. The resulting feed speed is 10.3 kg/hour, the capacity of the combustion chamber for sawdust is 3.4 kg, the average temperature in the fuel feeder is 40.41 °C, in the combustion chamber 414.57 °C, in the heat exchanger 79.80 °C, in the chimney 104.11 °C, in the furnace outlet channel 62.77 °C, in the channel after the fan 46.08 °C, the sawdust fuel consumption rate was 5.8 kg/hour and the furnace efficiency obtained in the study was 53.90%. The resulting hot air temperature can be used for drying grain.Key words:  design, efficiency furnace, mobile drying furnace, temperature